Lietuviškų knygų rinkinys Britų bibliotekoje - Navickienė, Aušra; Zmroczek, Janet (Knygotyra, 1998)
Lithuanian books make a part of the broader collection of books in Slavonic and other languages of Eastern Europe at the British Library. Though some attempts were made to investigate this collection from the very beginning of the 20th century, there are no comprehensive data about the Lithuanian books in this library.In this article the authors present the results of the latest investigation of the collection, which has unique copies of books very important for Lithuanian culture. The aim of investigation was to look more accurately at the Lithuanian books, that were published in the period of 1547–1904, to clear up the history of such collection. The search for the printings was conducted by the A series volumes of Lithuanian national retrospective bibliography and their additions in the printed catalogues of the British Library as well as in catalogue in machine-readable form. The copies, which were found, were examined de visu. Information about every copy – its acquisition, the sources, its previous life in society – was gathered according to the documents of the British Library archive. Due to time pressure, the investigation was limited to Lithuanian books and brochures, which were published during 1547–1904. Periodical materials and Lithuanica were not covered by the study. Besides books and brochures, old Lithuanian texts, which were published in foreign language books were investigated, too.On the whole 229 copies of Lithuanian printings and 23 old Lithuanian texts in foreign language books have been found. Of them 193 copies were investigated de visu. Some books could not be found because they might have been destroyed during the Second World War together with many other books.In comparison to D. Robinson’s bibliography the list of Lithuanian books was supplemented by 137 new printings of which 17 copies had been published during 1589–1864 and the other 120 copies – during 1865–1904. During the investigation data about every book were gathered and analysed. The studied books are presented in alphabetical list. The list contains abridged bibliographical description, the signature of British Library, information on physical condition, marks of books; information about the sources of acquisition of the copy – the date of acquisition, the sources and the way of acquisition; the bibliographical sources and the literature about the book. Due to volume limitations, in this article the authors present only a part of list, which contains Lithuanian books and printed material with Lithuanian texts of 1547–1864. (The continuation of list which contains Lithuanian books of 1865–1904 is published in the 33rd volume of „Knygotyra“.)On the ground of this list the authors analyse the collection of Lithuanian books according to the following aspects: the date of publication, the topics covered, the rarity of copies, the date of acquisition, the resources and the ways of acquisition.